1998
DOI: 10.1152/ajprenal.1998.274.5.f966
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the polymeric immunoglobulin receptor by water intake and vasopressin in the rat kidney

Abstract: The polymeric immunoglobulin receptor (pIgR) transports polymeric immunoglobulins (IgA) from the basolateral to the apical surface of epithelial cells. At the apical surface, its amino-terminal domain, termed secretory component (SC), is proteolytically cleaved and released either unbound (free SC) or bound to IgA. We examined the effects of changes in water balance and vasopressin on the production and secretion of the pIgR in the rat kidney in vivo. Water deprivation induced a 2.7-fold increase in the pIgR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…We are the first to demonstrate that infection caused by P(ϩ) E. coli decreases pIgR expression in the cortical nephron segments. The distribution of pIgR protein seems to be similar to that of the normal rat kidney, in which we have demonstrated that pIgR protein is preferentially expressed near the luminal surface of the thick ascending limb and throughout some proximal tubules (11). The decreased pIgR staining in the cortical tubules of the P(ϩ) E. coli-infected mice suggests that pIgR protein is depleted from the apical storage vesicles of the renal epithelia, where it has been shown clearly to be stored by electron microscopy in normal mice (33), and is consistent with our findings of decreased pIgR protein levels by Western blot in the P(ϩ) E. coli-infected group at 48 h. Hence, the depletion of pIgR protein in the kidney cortex of pyelonephritis animals at 48 h (Figure 4) results from the combined effects of decreased pIgR RNA levels ( Figure 2) and the continued excretion of SC (cleaved fragment of pIgR) either attached to IgA ( Figure 5) or as FSC.…”
Section: E Coli Expressing P Fimbriae Decrease Pigr Protein Levels Isupporting
confidence: 59%
See 3 more Smart Citations
“…We are the first to demonstrate that infection caused by P(ϩ) E. coli decreases pIgR expression in the cortical nephron segments. The distribution of pIgR protein seems to be similar to that of the normal rat kidney, in which we have demonstrated that pIgR protein is preferentially expressed near the luminal surface of the thick ascending limb and throughout some proximal tubules (11). The decreased pIgR staining in the cortical tubules of the P(ϩ) E. coli-infected mice suggests that pIgR protein is depleted from the apical storage vesicles of the renal epithelia, where it has been shown clearly to be stored by electron microscopy in normal mice (33), and is consistent with our findings of decreased pIgR protein levels by Western blot in the P(ϩ) E. coli-infected group at 48 h. Hence, the depletion of pIgR protein in the kidney cortex of pyelonephritis animals at 48 h (Figure 4) results from the combined effects of decreased pIgR RNA levels ( Figure 2) and the continued excretion of SC (cleaved fragment of pIgR) either attached to IgA ( Figure 5) or as FSC.…”
Section: E Coli Expressing P Fimbriae Decrease Pigr Protein Levels Isupporting
confidence: 59%
“…Northern blot of total RNA was performed using a formaldehyde 1% agarose gel and transferred to a nylon membrane (Schleicher & Schuell, Keene, NH) as described (11). We used the 2.2-kb SacI fragment of the full-length cDNA probe for mouse pIgR mRNA provided by Charlotte Kaetzel (25) for Northern hybridization analysis of pIgR.…”
Section: Total Rna Isolation and Northern Hybridization Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, significant levels of SC were seen in tubular epithelial cells, but not glomeruli, from 51 patients with various forms of renal damage (Dobrin et al, 1975), and levels of urinary SIgA and free SC were found to be elevated in acute pyelonephritis (Svanborg Edén et al, 1985;Greenwell et al, 1995). In subsequent studies using more sensitive methods, pIgR mRNA and protein were detected in normal rat kidney, and levels were elevated after water deprivation, treatment with vasopressin, or ischemia (Rice et al, 1998(Rice et al, , 1999. Taken together, these data suggest that pIgR is normally expressed at low levels in the kidney but may be elevated in renal disease.…”
Section: Tissue-specific Expression Of Pigrmentioning
confidence: 99%